Using the potential of plant farming to strengthen the energy security of territorial communities - Serebrennikov, B.; Sirikov, O.; Kotysh, A.; Serebrennikov, S. (Energy and Automation, 2024)
In Ukraine, there is a growing need to strengthen the reliability of energy supply at the regional level due to the development of effective strategies for developing and utilizing local bioenergy. Comparative analysis of territories by the bioenergetic potential of crops helps to identify the most productive of them and determine the drivers for establishing the bioenergetic potential of each territorial community (TC) in its inherent natural and climatic conditions.The study aims to increase the level of energy independence of TCs by determining the distribution of bioenergy potential and forecasting the bio-productivity of local crop production. In the example of 49 TCs of the Kirovohrad region, the amount of secondary plant material that can be obtained from arable land for biofuel production was evaluated. The statistical analysis was carried out for the pre-war period of 2019-2021, covering 12 key crops: spring and winter wheat and barley, rye, oats, rapeseed, millet, sunflower, corn, soybeans, and buckwheat.The amount of collected non-productive part of the plants was determined indirectly, based on the correlational recalculation of statistical data on the gross crop yield. The distribution of energy biopotential among TCs was calculated as follows: the average yield of the grain part of crops over three years was determined based on the area of crops and the gross yield, from which, using correlation coefficients, the mass of unproductive plant parts was calculated; energy productivity of plants was assessed by calorific value; and, finally, net bio-productivity was determined, taking into account losses and non-energy use of bio-raw material.The key crops were identified, and a map of the distribution of bioenergy resources was created for each TC. According to the map, wheat, corn, barley, sunflower, oats, and rye were the most energy-intensive for the steppe and forest-steppe. In particular, wheat and corn account for about 40...50 % of the total energy potential of plant biomass (gross). At the same time, the energy productivity of wheat exceeds that of corn by 35 % on average and that of sunflower by 90%. In most TCs, corn is almost twice as energy efficient as sunflower.After considering the losses and costs of plant mass for non-energy needs, a refined map of the distribution of net bioenergy potential was created. Under such conditions, the leadership goes to corn, which surpassed wheat in terms of energy productivity by 16% in all TCs.According to the adjusted distribution of net bioenergy potential, the three TCs lead with EAV.N = 1.27...1.36 t.с.f./ha with priority crops: corn, wheat, sunflower, and soy. The lowest bioenergy potential has the three TCs with EAV.N = 0.85...0.99 t.с.f./ha, although, for certain crops (corn, sunflower, soy), they reach relatively high indicators (1.17...2.22 t.с.f./ha).A comparison of the potentials of total EAV = 1.90 t.с.f./ha and net EAV.N = 1.11 t.с.f./ha reveals that the achievable bioenergy resource is only 52.5 % of the calculated one. Therefore, it is necessary to more actively implement the latest technologies to minimize losses and non-energy use of biomass. Key words: bioenergy resources, crops, energy productivity, territorial distribution of energy potential